2020
DOI: 10.3389/fpsyg.2020.615575
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Evaluation of Digitally Reproduced Art Images

Abstract: Most people encounter art images as digital reproductions on a computer screen instead of as originals in a museum or gallery. With the development of digital technologies, high-resolution artworks can be accessed anywhere and anytime by a large number of viewers. Since these digital images depict the same content and are attributed to the same artist as the original, it is often implicitly assumed that their aesthetic evaluation will be similar. When it comes to the digital reproductions of art, however, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“… Skelton and Franklin (2020) reported that when colors were highly saturated, infants look longer at colors that adults prefer, and infant looking time and adult preference were highest for blue hues and are lowest for green/yellow hues. Reymond et al (2020) argued that digital reproduction of artworks can vary greatly in saturation; however in an empirical study where color saturation was manipulated, this did not exert major influences on liking. Specker et al (2018 , p. 48) argued that variation in associations connected to hue are often due to cultural variation and represent influences of language on color discrimination ( Winawer et al, 2007 ; Regier and Kay, 2009 ), cultural differences in affective meaning, as well as associations related to different hues ( Saito, 1996 ).…”
Section: Variables Affecting Image Aesthetics Of Mobile Phone Photogr...mentioning
confidence: 91%
“… Skelton and Franklin (2020) reported that when colors were highly saturated, infants look longer at colors that adults prefer, and infant looking time and adult preference were highest for blue hues and are lowest for green/yellow hues. Reymond et al (2020) argued that digital reproduction of artworks can vary greatly in saturation; however in an empirical study where color saturation was manipulated, this did not exert major influences on liking. Specker et al (2018 , p. 48) argued that variation in associations connected to hue are often due to cultural variation and represent influences of language on color discrimination ( Winawer et al, 2007 ; Regier and Kay, 2009 ), cultural differences in affective meaning, as well as associations related to different hues ( Saito, 1996 ).…”
Section: Variables Affecting Image Aesthetics Of Mobile Phone Photogr...mentioning
confidence: 91%
“…In recent years, with the deepening of the research on image processing technology, image perception technology has attracted more and more researchers' attention, which has made great achievements and progress in image perception algorithms. Image perception algorithm maps the characteristic data of an image to a short string code, which is a compact representation based on the image content [7,8]. It makes the visually identical image map to the same or similar image, and different images map to different degrees [9].…”
Section: Introductionmentioning
confidence: 99%
“…The images were downloaded from the artist’s own website, from museum’s websites, or from auction houses. As such, the images were expected to represent the most faithful reproductions of the original photograph’s contrast and color (Reymond et al, 2020). Context images were selected from the OASIS Image Set (Open Affective Standardized Image Set; Kurdi et al, 2017) and consisted of horizontal format (nonart) color photographs.…”
Section: Methodsmentioning
confidence: 99%